Use of MALDI-TOF mass spectrometry for specificity studies of biomedically important proteases. Issue 3 (2002) - Siigur Siigur, Jüri Jüri; Trummal Trummal, Katrin Katrin; TÕnismägi TÕnismägi, Külli Külli; Samel Samel, Mari Mari; Siigur Siigur, Ene Ene; Vija Vija, Heikki Heikki; Tammiste Tammiste, Indrek Indrek; Subbi Subbi, Juhan Juhan
Abstract : Proteases play crucial role starting from fertilization until to cell death. Our studies of the two Viperidae venoms (Levantine viper Vipera lebetina, Common viper Vipera berus ) have demonstrated the existence of biomedically important proteases, both coagulants and anticoagulants that may be useful as diagnostic tools or potential therapeutics. We showed that venoms of both snakes contain: (i) metalloproteases and serine proteases that degrade fibrinogen, but not fibrin; (ii) factor X activators (VLFXA, VBFXAE); (iii) bradykinin‒releasing serine proteases. Additionally Vipera lebetina snake venom contains thrombolytic fibrin degrading metalloenzyme (lebetase), HUVEC cell apoptosis inducing metalloprotease (VLAIP), factor V activator (VLFVA), thermostable β-fibrinogenase and α-fibrinogenase which has no homolog among known serine proteases. We examined the activity of snake venom proteases against bradykinin, substance P, insulin B‒chain and 6–10 amino acid residues containing peptides synthesized according to potential cleavage regions of fibrinogen, factor X, factor IX, factor V, α2 ‒macroglobulin bait region and pregnancy zone protein (PZP). We used MALDI TOF mass spectrometry technique for the discovery and identification of peptides released by protease hydrolysis. The sensitive and quick MALDI-TOF mass spectrometry methodology allows us to obtain the primary information about the substrate specificity of different proteases against various peptides and proteins.